Piezoelectric films containing ionic liquids and electrophoretic display films containing piezoelectric films - Patents.com
By incorporating less than 10% ionic liquid into PVDF, the piezoelectric film achieves high beta phase concentration without stretching, resulting in a thin, transparent, and flexible film suitable for security markers and authentication indicators.
Patent Information
- Application Number
- JP2024549653
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-28
- Filing Date
- 2023-02-22
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-02-22
AI Technical Summary
Existing piezoelectric polymer films, such as those made from PVDF, require stretching to achieve a sufficient beta phase concentration, leading to heterogeneity in film thickness and optical distortion.
A piezoelectric film is formed by combining polyvinylidene fluoride (PVDF) with less than 10% of an ionic liquid, which increases the beta phase concentration without the need for stretching, resulting in a thin, transparent, and flexible film.
The resulting piezoelectric film is thin, transparent, and maintains uniform thickness, eliminating optical distortions and enabling the generation of well-functioning security markers and authentication indicators without external power.
Smart Images

Figure 2025507654000001_ABST
Abstract
Description
[Background technology]
[0001] (Reference to Related Application) This application claims priority to U.S. Provisional Application No. 63 / 314,702, filed February 28, 2022. All patents and publications disclosed herein are incorporated by reference in their entirety.
[0002] Electrophoretic displays (EPDs) are non-emissive devices based on electrophoresis of charged pigment particles dispersed in a solvent or solvent mixture. The displays typically comprise two electrodes placed opposite each other, which provide an electric field to drive the movement of the charged pigment particles. One of the electrodes is usually transparent. When a voltage difference is applied between the two electrodes, the pigment particles migrate to one side or the other, causing either the color of the pigment particles or the color of the solvent (if colored) to be seen from the viewing side. Electrophoretic fluids typically include a non-polar solvent and one or more sets of charged particles. The particles may have different optical properties (colors), different charges (positive or negative), different charge magnitudes (zeta potentials), and / or different absorptive properties (broadly, light absorbing, broadly, light reflecting, or selectively absorbing or reflecting). In cases where there are multiple sets of particles with opposite charge polarity, application of an electric field can cause one set of particles to appear at the viewing surface while other particles are driven away from the viewing surface.
[0003] Many electrophoretic displays are bistable, meaning that their optical state persists after the activating electric field is removed. Bistability is primarily due to an induced dipole charge layer that develops around the charged pigment due to complex interactions between the pigment, charge control agent, and free polymer dispersed in a solvent. Bistable displays can persist for years in the last addressed optical state before being switched again with the application of a new driving field.
[0004] Driving an electrophoretic display requires a power source to provide an electric field between the electrodes. The power source is typically a battery, which provides power to the electrodes via drive circuitry. One or more electrodes may be incorporated into an active matrix backplane. The power source may be, for example, a photovoltaic cell, a fuel cell, or a power source that operates from wall currents.
[0005] The power source can also be a piezoelectric element, which generates an electric charge through physical motion or thermal expansion, as described in U.S. Patent No. 5,930,026, which is incorporated by reference in its entirety. Since electrophoretic displays are typically constructed as films, it is preferable to bond the electrophoretic film to a piezoelectric film. The resulting display is thinner and more flexible. However, only piezoelectric polymers can be made into films that can be bonded to electrophoretic films. In general, crystalline piezoelectric materials are very brittle and not suitable for incorporation into electrophoretic displays.
[0006] Such piezoelectric polymer films, including polyvinylidene fluoride (PVDF), polyvinylidene chloride (PVDC), polyamide, and parylene-C, require a high relative concentration of polarizable regions to be useful. For example, in PVDF, the fluorine atoms in the polymer chains must be locally aligned to achieve a suitable piezoelectric effect. However, being a polymer, when melted, the PVDF chains typically assume their lowest energy state, known as the alpha phase, in which the fluorine atoms are disturbed and can be as far away from each other as possible. The alpha phase of PVDF has very little piezoelectric response. Other phases, such as beta and gamma, have fluorine atoms primarily in the same direction and have much greater piezoelectric response. To achieve sufficient beta phase concentration, it is often necessary to stretch a piezoelectric polymer film such as PVDF after formation from the melt to induce domains of stress that increase the polarizability. The stretched polymer film can then be poled to align the beta phase to increase the piezoelectric response, i.e., the strength of the local electric field.
[0007] However, stretching the polymer film after formation introduces inhomogeneities into the film thickness. Stretching can also cause the film to "crack" and distort the light passing through it. It is possible to avoid stretching the piezoelectric polymer film by adding charged inorganic particles, such as clay and carbon black, that increase the local polarizability. However, at the concentration scale where the charged additive particles are effective, composite piezoelectric polymer films typically lose their transparency due to a combination of scattering and absorption by the additive particles. Thus, it is very difficult to produce thin transparent piezoelectric films with uniform thickness and sufficient beta (or gamma) phase to be useful for piezoelectric applications. Summary of the Invention [Means for solving the problem]
[0008] Disclosed herein are piezoelectric films formed from a mixture of polyvinylidene fluoride (PVDF) and an ionic liquid, and methods for making such piezoelectric films. Due to the presence of ionic liquid, the resulting piezoelectric film has a higher concentration of beta phase than PVDF alone, and the film does not need to be stretched to increase the proportion of beta phase. Thus, the piezoelectric films can be made thin and transparent, as discussed below, and may be suitable for poling, for example, with an electric field. Because piezoelectric films are not stretched, they do not suffer from optical stretching distortion, fracturing, and thickness variations across the film. Such thickness variations would result in different optical responses in low-voltage electrophoretic films when such films are bonded to piezoelectric films. Thus, the piezoelectric films described herein enable the creation of security markers, authentication marks, indicators, and strain sensors that work well with electrophoretic films. Such films do not require any external power. They can be switched between optical states using simple mechanical motion (see, for example, Figures 1A and 1B). Nonetheless, it is viable to use the piezoelectric films described herein with powered electrophoretic displays.
[0009] In a first aspect, the invention includes a piezoelectric film comprising polyvinylidene fluoride (PVDF) and less than 10% (w / w) of an ionic liquid. In some embodiments, the piezoelectric film is less than 10 μm thick. In some embodiments, the ionic liquid comprises an alkyl-substituted imidazolium cation, an alkyl-substituted pyridinium cation, a pyridine-derived N-heterocyclic cation, a fluorinated counter anion, a sulfated counter anion, a dicyanamide (N(CN)2), a quaternary ammonium cation, or a combination thereof. In some embodiments, the alkyl-substituted imidazolium cation is 1-butyl-3-methylimidazolium (BMIM), 1-ethyl-3-methylimidazolium (EMIM), 1-butyl-2,3-dimethylimidazolium (DBMIM), 1-octyl-3-methylimidazolium (OMIM), 1,3-di(N,N-dimethylaminoethyl)-2-methylimidazolium (DAMI), 1-decyl-3-methylimidazolium (DMIM), 1-dodecyl-3-methyl-dodecylimidazolium, and 1-butyl-2,3-dimethylimidazolium (BMMIM). In some embodiments, the pyridine-derived N-heterocyclic cation is 4-methyl-N-butyl-pyridinium (MBPy) or N-octylpyridinium (C8Py). In some embodiments, the fluorinated counter anion is tetrafluoroborate (BF4), hexafluorophosphate (PF6), bis-trifluoromethanesulfonimide (NTf2), or trifluoromethanesulfonic acid (OTf). In some embodiments, the quaternary ammonium cation is tetraethylammonium (TEA) or tetrabutylammonium (TBA). In some embodiments, the sulfated counter anion is hydrogen sulfate (HSO4), methyl sulfate (MeOSO3), trifluoromethyl sulfate (CF3OSO3), ethyl sulfate (EtOSO3), or perfluoroethyl sulfate (CF3CF2OSO3). In some embodiments, the ionic liquid is 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIM) (BF4). In some embodiments, the film is light-transmitting.In some embodiments, the piezoelectric film further comprises a copolymer selected from trifluoroethylene (TrFE), hexafluoropropylene (HFP), and chlorotrifluoroethylene (CTFE).
[0010] In some embodiments, the electrophoretic display film can be produced with a thickness (top to bottom) of less than 100 μm and includes a first adhesive layer, an electrophoretic medium layer, a patterned PVDF film with zones of differential polarization, and a flexible light-transmitting electrode layer. The PVDF film can be any of the types described above. In some embodiments, the electrophoretic medium layer includes a plurality of microcapsules containing a non-polar fluid and charged pigment particles, the charged pigment particles moving toward or away from the piezoelectric layer when the piezoelectric layer is bent, and the microcapsules are bonded to each other using a polymeric binder. In some embodiments, the electrophoretic medium layer includes a plurality of microcells containing a non-polar fluid and charged pigment particles, the charged pigment particles moving toward or away from the piezoelectric layer when the piezoelectric layer is bent, and the non-polar fluid and charged pigment particles are sealed within the microcells using a sealing layer. In some embodiments, the film is less than 50 μm thick. In some embodiments, the patterned piezoelectric layer comprises polyvinylidene fluoride (PVDF). In some embodiments, the PVDF is poled to produce zones of differential polarization. In some embodiments, the flexible light-transmitting electrode layer comprises a metal oxide comprising tin or zinc. In some embodiments, the flexible light-transmitting electrode layer comprises poly(3,4-ethyleneoxythiophene) (PEDOT). In some embodiments, the invention includes an electrophoretic display film assembly comprising a release sheet bonded to an electrophoretic display film as described above, the release sheet being bonded to a first adhesive layer. In some embodiments, a second adhesive layer is bonded to the flexible light-transmitting electrode layer, and a second release sheet is bonded to a second adhesive layer. In some embodiments, the electrophoretic display film can be produced with a thickness (top to bottom) of less than 100 μm and comprises a first adhesive layer, a patterned PVDF film comprising zones of differential polarization, an electrophoretic medium layer, and a flexible light-transmitting electrode layer.The patterned PVDF film can be made according to any of the PVDF films described above. In some embodiments, the electrophoretic display film can be produced with a thickness (top to bottom) of less than 100 μm and includes an adhesive layer, an electrophoretic medium layer, a patterned PVDF film with zones of differential polarization, and a conductive adhesive layer. The patterned PVDF film can be made according to any of the PVDF films described above.
[0011] In a second aspect, the present invention includes a method of making a piezoelectric film comprising polyvinylidene fluoride (PVDF). The method includes providing a powdered or pelleted polymer comprising PVDF, combining an ionic liquid with PVDF at less than 10% (ionic liquid weight / PVDF weight) to form a mixture, diluting the mixture with an aprotic solvent to form a slurry, casting the slurry on a release substrate to form a slurry film, heating the slurry film to form a piezoelectric film comprising PVDF, and removing the piezoelectric film comprising PVDF from the release substrate. In some embodiments, the aprotic solvent comprises dimethylformamide (DMF), dimethylacetamide, or 1-methyl-2-pyrrolidone. In some embodiments, the powdered or pelleted polymer comprising PVDF further comprises a copolymer selected from trifluoroethylene (TrFE), hexafluoropropylene (HFP), and chlorotrifluoroethylene (CTFE). In some embodiments, the piezoelectric film is less than 10 μm thick. In some embodiments, the ionic liquid comprises an alkyl-substituted imidazolium cation, an alkyl-substituted pyridinium cation, a pyridine-derived N-heterocyclic cation, a fluorinated counter anion, a sulfated counter anion, a dicyanamide (N(CN)2), a quaternary ammonium cation, and combinations thereof. In some embodiments, the alkyl-substituted imidazolium cation is 1-butyl-3-methylimidazolium (BMIM), 1-ethyl-3-methylimidazolium (EMIM), 1-butyl-2,3-dimethylimidazolium (DBMIM), 1-octyl-3-methylimidazolium (OMIM), 1,3-di(N,N-dimethylaminoethyl)-2-methylimidazolium (DAMI), 1-decyl-3-methylimidazolium (DMIM), 1-dodecyl-3-methyl-dodecylimidazolium, and 1-butyl-2,3-dimethylimidazolium (BMMIM). In some embodiments, the pyridine-derived N-heterocyclic cation is 4-methyl-N-butyl-pyridinium (MBPy) or N-octylpyridinium (C8Py).In some embodiments, the fluorinated counter anion is tetrafluoroborate (BF4), hexafluorophosphate (PF6), bis-trifluoromethanesulfonimide (NTf2), or trifluoromethanesulfonic acid (OTf). In some embodiments, the quaternary ammonium cation is tetraethylammonium (TEA) or tetrabutylammonium (TBA). In some embodiments, the sulfated counter anion is hydrogen sulfate (HSO4), methyl sulfate (MeOSO3), trifluoromethyl sulfate (CF3OSO3), ethyl sulfate (EtOSO3), or perfluoroethyl sulfate (CF3CF2OSO3). In some embodiments, the ionic liquid is 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIM) (BF4). In some embodiments, the film is light-transmitting. In some embodiments, less than 1% (ionic liquid weight / PVDF weight) ionic liquid is combined with PVDF to produce a mixture.
[0012] In some embodiments, an electrophoretic display film can be constructed with a PVDF film made using the method described above. The electrophoretic display film can be made by bonding a film of polyvinylidene fluoride (PVDF) to a polymer film comprising an acrylate, vinyl ether, or epoxide to produce a piezoelectric microcell precursor film, bonding the piezoelectric microcell precursor film to a flexible light-transmitting electrode layer, bonding the light-transmitting electrode layer to a first release film using a first adhesive layer, embossing the piezoelectric microcell precursor film to produce an array of microcells, the microcells having a bottom, a wall, and a top opening, filling the microcells with an electrophoretic medium through the top opening, and sealing the top openings of the filled microcells with a water-soluble polymer. In some embodiments, the method further includes bonding the water-soluble polymer to a second release film using a second adhesive layer. In some embodiments, the method further includes removing the first release film to produce an electrophoretic display film that is less than 100 μm thick. In some embodiments, the electrophoretic medium layer comprises a plurality of microcells containing a non-polar fluid and charged pigment particles, the charged pigment particles moving toward or away from the piezoelectric layer when the piezoelectric layer is bent, and the non-polar fluid and charged pigment particles are sealed within the microcells using a sealing layer. In some embodiments, the PVDF is polarized to create zones exhibiting differences in polarization. In some embodiments, the flexible light-transmissive electrode layer comprises a metal oxide comprising tin or zinc. In some embodiments, the flexible light-transmissive electrode layer comprises poly(3,4-ethyleneoxythiophene) (PEDOT). In some embodiments, the polyvinylidene fluoride film is patterned with an electric field to create areas of different polarization. In some embodiments, the method further comprises patterning the completed electrophoretic display film with an electric field to create areas of different polarization in the polyvinylidene fluoride film. [Brief description of the drawings]
[0013] [Figure 1A] 1A shows a side view of a piezoelectric display film of the present invention, which includes star-shaped areas of differential polarization. Three exemplary positions are shown from the side: convex, neutral, and concave. The total thickness of the piezoelectric display film can be less than 100 μm, such as less than 50 μm, such as less than 25 μm.
[0014] [Figure 1B] 1B shows a top view of a piezoelectric display film of the present invention, which includes star-shaped areas of differential polarization. Three exemplary positions are shown from above: convex, neutral, and concave. When the piezoelectric display film is bent, the areas of differential polarization result in oppositely charged particles appearing at the viewing surface.
[0015] [Figure 2A] FIG. 2A shows an exemplary thin layer of piezoelectric material on a substrate.
[0016] [Figure 2B] 2B illustrates how the strong electric field of a corona discharge can be used to create areas of differential polarization in a thin layer of piezoelectric material. By moving the piezoelectric material closer and farther from the discharge, the amount of polarization can be spatially controlled.
[0017] [Figure 2C] 2C illustrates how areas of differential polarization can be created in a thin layer of piezoelectric material by using the strong electric field of a corona discharge. A conductive mask is used to pattern the piezoelectric material to create areas of differential polarization.
[0018] [Figure 2D]FIG. 2D illustrates a polarization pattern that can be achieved using the methods of FIGS. 2B and 2C.
[0019] [Figure 3A] FIG. 3A illustrates a side view of a piezoelectric film poled in the A direction.
[0020] [Figure 3B] FIG. 3B illustrates a top view of a piezoelectric film poled in the A direction.
[0021] [Figure 3C] FIG. 3C illustrates a side view of a piezoelectric film poled in the G direction using a conductive mask.
[0022] [Figure 3D] FIG. 3D illustrates a top view of a piezoelectric film poled in the G direction using a conductive mask.
[0023] [Figure 4A] FIG. 4A shows an exemplary thin layer of piezoelectric microcell precursor film on a substrate.
[0024] [Figure 4B] 4B illustrates how the strong electric field of a corona discharge can be used to create areas of differential polarization within a thin layer of piezoelectric material of a piezoelectric microcellular precursor film. By moving the piezoelectric microcellular precursor film closer and farther from the discharge, the amount of polarization can be spatially controlled.
[0025] [Figure 4C] 4C illustrates a method of creating areas of differential polarization in a thin layer of piezoelectric material of a piezoelectric microcellular precursor film by using the strong electric field of a corona discharge. A conductive mask is used to pattern the piezoelectric material of the piezoelectric microcellular precursor film to create areas of differential polarization.
[0026] [Figure 4D] FIG. 4D illustrates a poling pattern in a piezoelectric microcellular precursor film that can be achieved using the methods of FIGS. 3B and 3C.
[0027] [Figure 5A] FIG. 5A is a schematic cross-sectional view of an embodiment of a piezoelectric film.
[0028] [Figure 5B] FIG. 5B is a schematic cross-sectional view of an embodiment of a piezoelectric film.
[0029] [Figure 5C] FIG. 5C is a schematic cross-sectional view of an embodiment of a piezoelectric film.
[0030] [Figure 5D] FIG. 5D is a schematic cross-sectional view of an embodiment of a piezoelectric film.
[0031] [Figure 6A] FIG. 6A is a schematic cross-sectional view of an embodiment of a piezoelectric phoretic display.
[0032] [Figure 6B] FIG. 6B is a schematic cross-sectional view of an embodiment of a piezoelectric phoretic display.
[0033] [Figure 7] FIG. 7 details a method for producing a piezophoretic film or (optionally) a display.
[0034] [Figure 8A] FIG. 8A is a schematic cross-sectional view of an embodiment of a piezoelectric film.
[0035] [Figure 8B] FIG. 8B is a schematic cross-sectional view of an embodiment of a piezoelectric film.
[0036] [Figure 9A]FIG. 9A is a schematic cross-sectional view of an embodiment of a piezoelectric film.
[0037] [Figure 9B] FIG. 9B is a schematic cross-sectional view of an embodiment of a piezoelectric film.
[0038] [Figure 10A] FIG. 10A is a schematic cross-sectional view of an embodiment of a piezoelectric phoretic display.
[0039] [Figure 10B] FIG. 10B is a schematic cross-sectional view of an embodiment of a piezoelectric phoretic display.
[0040] [Figure 10C] FIG. 10C is a schematic cross-sectional view of an embodiment of a piezoelectric phoretic display.
[0041] [Figure 11] FIG. 11 details a method for producing a piezoelectric film containing an ionic liquid.
[0042] [Figure 12] FIG. 12 shows the infrared spectrum of the piezoelectric film containing ionic liquid and a comparison with the native polymer and other methods of increasing the beta phase in polymers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0043] Disclosed herein are piezoelectric films that include ionic liquids and methods for making piezoelectric films that include ionic liquids. The resulting films have a higher level of beta phase and can be poled using an external field without additional processing such as stretching. The films are optically transparent. The films are generally flexible. Some films are less than 100 μm thick. In some embodiments, the piezoelectric films can be combined with electrophoretic media to produce piezoelectric films, and the resulting piezoelectric films can be patterned after fabrication using high voltage electric fields. This feature allows the end user of the piezoelectric film to address the piezoelectric material, for example, using corona discharge during production, which can include, for example, a bar code or serial number that is only visible when the piezoelectric film is manipulated. Such films are useful as security markers, authentication films, indicators, or sensors. The films are generally flexible. Some films are less than 100 μm thick. In some embodiments, the piezoelectric film is less than 50 μm and can be folded without breaking. Displays made with the film do not require an external power source.
[0044] The term "electro-optical" as applied to a material or display is used herein to refer to a material having first and second display states that differ in at least one optical property in its conventional sense in the imaging arts, and that is changed from its first display state to its second display state by application of an electric field to the material. The optical property is typically color perceptible to the human eye, but may be another optical property such as optical transmittance, reflectance, luminescence, or, in the case of displays intended for machine reading, pseudocolor in the sense of a change in reflectance of electromagnetic wavelengths outside the visible range.
[0045] The terms "bistable" and "bi-stable" are used herein in their conventional meaning in the art to refer to displays comprising display elements having first and second display states that differ in at least one optical property, such that after any given element is driven with an address pulse of finite duration to exhibit either a first or second display state, that state will persist after the address pulse is terminated for at least several times, e.g., at least four times, the minimum duration of the address pulse required to change the state of the display element. In U.S. Pat. No. 7,170,670, it is shown that some particle-based electrophoretic displays capable of gray scale are stable not only in their extreme black and white states, but also in their intermediate gray states, and the same is true for some other types of electro-optic displays. Displays of this type are appropriately referred to as "multistable" rather than bistable, but for convenience the term "bistable" may be used herein to cover both bistable and multistable displays.
[0046] The term "gray state" is used herein in its conventional sense in the imaging arts to refer to a state intermediate between two extreme pixel optical states, and does not necessarily imply a black-white transition between these two extreme states. For example, some of the E INK patents and published applications referenced below describe electrophoretic displays in which the extreme states are white and dark blue, such that the intermediate "gray state" is actually light blue. In fact, as already described, the change in optical state may not be a change in color at all. The terms "black" and "white" may be used hereinafter to refer to the two extreme optical states of the display, and should generally be understood to include extreme optical states that are not strictly black and white, such as the white and dark blue states mentioned above. The term "monochrome" may be used hereinafter to refer to a display or driving scheme that drives pixels to only their two extreme optical states, with no intervening gray states.
[0047] The term "pixel" is used herein in its conventional sense in the display art to mean the smallest unit of a display capable of generating all the colors the display itself can show. In a full-color display, each pixel typically consists of a number of sub-pixels, each of which can display less than all the colors the display itself can show. For example, in most conventional full-color displays, each pixel consists of a red sub-pixel, a green sub-pixel, a blue sub-pixel, and optionally a white sub-pixel, each of which can display a range of colors from black to the brightest version of its defined color.
[0048] Several types of electro-optical displays are known. One type of electro-optical display uses an electrochromic medium, for example in the form of a nanochromic film consisting of electrodes formed at least in part from a semiconducting metal oxide and a plurality of dye molecules attached to the electrodes that can reverse the color change. See, for example, O'Regan, B., et al., Nature 1991, 353, 737 and Wood, D., Information Display, 18(3), 24 (March 2002). See also Bach, U., et al., Adv. Mater., 2002, 14(11), 845. Nanochromic films of this type are also described, for example, in U.S. Patent Nos. 6,301,038, 6,870,657, and 6,950,220. This type of medium is also typically bistable.
[0049] Another type of electro-optic display is the electrowetting display developed by Philips and described in Hayes, RA, et al, "Video-Speed Electronic Paper Based on Electrowetting", Nature, 425, 383-385 (2003). It is shown in U.S. Patent No. 7,420,549 that such electrowetting displays can be bistable.
[0050] Another type of electro-optic display that has been the subject of intensive research and development for many years is the particle-based electrophoretic display, in which a plurality of charged particles move through a suspending fluid under the influence of an electric field. Electrophoretic displays can have attributes of good brightness and contrast, wide viewing angles, state bistability, and low power consumption when compared to liquid crystal displays.
[0051] An electro-optical device typically comprises a layer of electrophoretic material and at least two other layers arranged on opposite sides of the electrophoretic material, one of these two layers being an electrode layer. In most such displays, both layers are electrode layers, and one or both of the electrode layers are patterned to define the pixels of the display. For example, one electrode layer may be patterned into elongated row electrodes and the other into elongated column electrodes extending at right angles to the row electrodes, the pixels being defined by the intersections of the row and column electrodes. Alternatively, and more commonly, one electrode layer has the form of a single continuous electrode, and the other electrode layer is patterned into a matrix of pixel electrodes, each of which defines one pixel of the display. In another type of electrophoretic display, intended for use with a display and a separate stylus, print head, or similar movable electrode, only one of the layers adjacent to the electrophoretic layer comprises an electrode; the layer opposite the electrophoretic layer is typically a protective layer intended to prevent the movable electrode from damaging the electrophoretic layer.
[0052] Numerous patents and applications assigned to or in the name of Massachusetts Institute of Technology (MIT) and E Ink Corporation describe various techniques used in encapsulating electrophoretic and other electro-optic media. Such encapsulated media comprises a number of small capsules, each of which itself comprises an internal phase that contains electrophoretically movable particles in a fluid medium, and a capsule wall that surrounds the internal phase. Typically, the capsules are themselves held within a polymeric binder to form a coherent layer that is positioned between two electrodes. Techniques described in these patents and applications include: (a) electrophoretic particles, fluids, and fluid additives (see, e.g., U.S. Pat. Nos. 7,002,728 and 7,679,814); (b) capsules, binders, and encapsulation processes (see, e.g., U.S. Pat. Nos. 6,922,276 and 7,411,719); (c) films and subassemblies containing electro-optical materials (see, e.g., U.S. Pat. Nos. 6,982,178 and 7,839,564); (d) backplanes, adhesive layers, and other auxiliary layers and methods used in displays (see, e.g., U.S. Pat. Nos. 7,116,318 and 7,535,624); (e) color formation and color control (see, e.g., U.S. Pat. Nos. 7,075,502 and 7,839,564); (f) methods of driving displays (see, e.g., U.S. Patent Nos. 7,012,600 and 7,453,445); (g) display applications (see, e.g., U.S. Pat. Nos. 7,312,784 and 8,009,348); (h) non-electrophoretic displays (see U.S. Pat. Nos. 6,241,921, 6,950,220, 7,420,549, and 8,319,759, and U.S. Patent Application Publication No. 2012 / 0293858); (i) microcell structures, wall materials, and methods of forming the microcells (see, e.g., U.S. Pat. Nos. 7,072,095 and 9,279,906); (j) Methods for filling and sealing microcells (see, e.g., U.S. Pat. Nos. 7,144,942 and 7,715,088).
[0053] Many of the aforementioned patents and applications recognize that the walls surrounding the separate microcapsules in an encapsulated electrophoretic medium may be replaced by a continuous phase, thus giving rise to so-called "polymer-dispersed electrophoretic displays," in which the electrophoretic medium consists of a plurality of separate droplets of electrophoretic fluid and a continuous phase of polymeric material, and in which the separate droplets of electrophoretic fluid in such polymer-dispersed electrophoretic displays may be considered capsules or microcapsules even though no separate capsule membrane is associated with each individual droplet. See, for example, the aforementioned U.S. Patent No. 6,866,760. Thus, for purposes of this application, such polymer-dispersed electrophoretic media are considered a subspecies of encapsulated electrophoretic media.
[0054] A related type of electrophoretic display is the microcell electrophoretic display, also known as MICROCUP®. In a microcell electrophoretic display, the charged particles and fluid are not encapsulated in microcapsules, but instead are held within a plurality of cavities formed in a carrier medium, typically a polymeric film. See, e.g., U.S. Patent Nos. 6,672,921 and 6,788,449, both of which are incorporated by reference in their entirety.
[0055] Although electrophoretic media are often opaque (e.g., in many electrophoretic media, because the particles substantially block the transmission of visible light through the display) and may operate in a reflective mode, many electrophoretic displays can be made to operate in a so-called "obstructed mode" in which one display state is substantially opaque and one is light-transmitting. See, for example, U.S. Pat. Nos. 5,872,552, 6,130,774, 6,144,361, 6,172,798, 6,271,823, 6,225,971, and 6,184,856. Dielectrophoretic displays, which are similar to electrophoretic displays but rely on variations in electric field strength, can operate in a similar mode. See U.S. Pat. No. 4,418,346. Other types of electro-optic displays may also be capable of operating in the obscured mode. Electro-optic media operating in the shielding mode may be useful in multi-layer structures for full-color displays, in which at least one layer adjacent to the viewing surface of the display operates in the shielding mode to expose or conceal a second layer that is more remote from the viewing surface.
[0056] Encapsulated electrophoretic displays typically do not suffer from the clustering and settling failure modes of conventional electrophoretic devices, and offer additional advantages such as the ability to print or coat displays on a wide variety of flexible and rigid substrates. (The use of the word "printing" is intended to include all forms of printing and coating, including, but not limited to, pre-metered coating such as patch die coating, slot or extrusion coating, slide or cascade coating, curtain coating, roll coating such as knife-over-roll coating, forward and reverse roll coating, gravure coating, dip coating, spray coating, meniscus coating, spin coating, brush coating, air knife coating, silk screen printing processes, electrostatic printing processes, thermal printing processes, inkjet printing processes, electrophoretic deposition (see U.S. Pat. No. 7,339,715), and other similar techniques.) Thus, the resulting display can be flexible. Furthermore, because the display medium can be printed using a variety of methods, the display itself can be made inexpensively.
[0057] The aforementioned U.S. Patent No. 6,982,178 describes a method for fabricating solid electro-optic displays (including particle-based electrophoretic displays) that is well adapted for mass production. Essentially, this patent describes a so-called "front plane laminate" ("FPL"), which comprises, in order, a light-transmitting conductive layer, a layer of a solid electro-optic medium in electrical contact with the conductive layer, an adhesive layer, and a release sheet. Typically, the light-transmitting conductive layer may be supported on a light-transmitting substrate, which is preferably flexible in the sense that the substrate may be manually rolled around a 10 inch (254 mm) diameter drum (for example) without permanent deformation. The term "optically transparent" is used in this patent and specification to mean that the layer so designated transmits sufficient light to enable an observer looking through the layer to observe a change in the display state of the electro-optic medium, usually as viewed through the conductive layer and adjacent substrate (if present); if the electro-optic medium exhibits a change in reflectance at non-visible wavelengths, the term "optically transparent" should of course be interpreted to refer to the transmission of the relevant non-visible wavelengths. The substrate will typically be a polymeric film, usually having a thickness within the range of about 1 to about 25 mils (25 to 634 μm), preferably about 2 to about 10 mils (51 to 254 μm). The conductive layer may conveniently be a thin metal or metal oxide layer, for example, aluminum or ITO, or may be a conductive polymer. Poly(ethylene terephthalate) (PET) films coated with aluminum or ITO are commercially available, for example as "aluminized Mylar" from EI du Pont de Nemours & Company (Wilmington Del.) ("Mylar" is a registered trademark), and such commercial materials can be used with good results in front plane laminations.
[0058] Assembly of an electro-optic display using such a front plane laminate can be accomplished by removing the release sheet from the front plane laminate and contacting the adhesive layer with the backplane under conditions effective to cause the adhesive layer to adhere to the backplane, thereby securing the adhesive layer, layer of electro-optic medium, and conductive layer to the backplane. This process is well suited to mass production, as the front plane laminate can typically be mass produced using roll-to-roll coating techniques and then cut into pieces of any size required for use with a particular backplane.
[0059] No. 7,561,324 describes a so-called "dual release sheet," which is essentially a simplified version of the front plane laminate of the aforementioned U.S. Pat. No. 6,982,178. One form of the dual release sheet comprises a layer of a solid electro-optic medium sandwiched between two adhesive layers, one or both of which are covered by a release sheet. Another form of the dual release sheet comprises a layer of a solid electro-optic medium sandwiched between two release sheets. Both forms of the dual release film are intended for use in a process generally similar to the process for assembling an electro-optic display from the front plane laminate already described, but involving two separate laminations, typically in a first lamination the dual release sheet is laminated to a front plane electrode to form a front plane assembly, and then in a second lamination the front plane assembly is laminated to a backplane to form the final display, although the order of these two laminations may be reversed, if desired.
[0060] The subject matter presented herein particularly relates to a piezoelectric display structural design, which does not require a power source (e.g., a battery or wired power supply, a photovoltaic source, etc.) for the electrophoretic display to operate. The assembly of such an electrophoretic display is therefore simplified. In some embodiments, the piezoelectric material and the electrophoretic medium are directly laminated together. The electrophoretic medium may be contained within a microcell, a microcapsule, as described above, or the electrophoretic medium may be dispersed in a polymer matrix. In some embodiments, the piezoelectric material is poled (i.e., written) using a high-voltage electric field after the piezoelectric film or piezoelectric display is produced, as discussed below.
[0061] Piezoelectricity is an electric charge that accumulates in a solid material in response to an applied mechanical stress. Suitable polymeric materials for the subject matter disclosed herein include polyvinylidene fluoride (PVDF), polyvinylidene chloride (PVDC), polyamide, parylene-C. The piezoelectric films and displays described herein use piezoelectricity to drive charged pigments of an electrophoretic medium. Thus, when a piezoelectric material bonded to an electrophoretic medium layer is manipulated, the color of the electrophoretic material at the viewing surface changes. For example, by bending or introducing stress into a piece of piezoelectric material, a voltage can be generated, which can be utilized to cause the color pigments of the electrophoretic material to move. If segments of piezoelectric material with different polarizations are used, or areas of differential polarization are created in the piezoelectric film, an electrophoretic medium with two types of oppositely charged pigments can be used to create patterns with high contrast ratios, as shown in Figures 1A and 1B. As used herein, the term "contrast ratio" (CR) in reference to electro-optic displays (e.g., electrophoretic displays) is defined as the ratio of luminance of the brightest color (white) to the darkest color (black) that the display can produce. Typically, a high contrast ratio, or CR, is a desirable aspect of a display.
[0062] 1A and 1B illustrate side and top views of an exemplary piezoelectric phoretic display 100 according to the subject matter disclosed herein. In this embodiment, a piezoelectric material of the present invention is laminated to an electrophoretic medium layer (discussed below), and one or more electrodes are included to provide a suitable electric field to drive the electrophoretic particles toward (or away from) a viewing surface. In the embodiment shown in FIGS. 1A and 1B, the second area 120 of the piezoelectric film of the piezoelectric phoretic display 100 is polarized in the opposite direction to the first area 110, so that when the piezoelectric phoretic display 100 is manipulated from a neutral state (position 2) to either a first (position 1) or second (position 3) optical state, the first and second areas (110, 120) will achieve different colors within the two areas. In the case of an electrophoretic medium with a set of black and white oppositely charged particles, a high contrast image will be formed, for example, as shown in FIG. 1B. Because the first and second areas of piezoelectric material (110, 120) can be polarized with good resolution (as discussed below), various images / information can be encoded to "appear" when the piezoelectric phoretic display 100 is manipulated. For example, a security ribbon can be generated to exist in a neutral state as a gray strip, but when the security ribbon is bent, the ribbon will display a security seal, such as the star shape shown in FIG. 1B. Of course, the security seal could alternatively include a barcode, a number, a word, a phone number, and an internet address, a QR code, a photograph, a halftone image, or a logo.
[0063] The piezoelectric film of the present invention comprises a piezoelectric polymer and less than 10% ionic liquid. The piezoelectric film has a sufficient amount of polarizable polymer domains to be useful as a piezoelectric material without the need for stretching / pulling or heat treatment such as annealing. The piezoelectric polymer can be polyvinylidene fluoride (PVDF), polyvinylidene chloride (PVDC), polyamide, parylene-C, or combinations thereof, however, PVDF is preferred as it is commercially available in powder and pellet form, for example, from Sigma Aldrich or Arkema. A preferred formulation is available under the trade name KYNAR®. PVDF can include copolymers such as trifluoroethylene (TrFE), hexafluoropropylene (HFP), and chlorotrifluoroethylene (CTFE). PVDF copolymers are also available as raw materials, however, PVDF copolymers are typically 100-10,000 times more expensive than simple PVDF. Ionic liquid may be present in the final film at a concentration of 10% or less by weight of ionic liquid to polymer, but the active piezoelectric film is with a concentration of 5% or less by weight of ionic liquid, for example, 2% or less by weight of ionic liquid, for example, 1% or less by weight of ionic liquid, for example, 0.5% or less by weight of ionic liquid, for example, 0.1% or less by weight of ionic liquid, for example, 500 ppm or less by weight of ionic liquid, for example, 250 ppm or less by weight of ionic liquid, for example, 100 ppm or less by weight of ionic liquid. Piezoelectric films can be made very thin, for example, 10 μm or less, for example, 7 μm or less, for example, 5 μm or less, for example, 3 μm or less, for example, about 1 μm thick. Using such films, for example, as discussed below, it is possible to produce piezoelectric electrophoretic films of 100 μm or less.
[0064] Suitable ionic liquids for incorporation into the piezoelectric films of the present invention include alkyl-substituted imidazolium cations, alkyl-substituted pyridinium cations, pyridine-derived N-heterocyclic cations, fluorinated counter anions, sulfated counter anions, dicyanamide (N(CN)2), quaternary ammonium cations, or combinations thereof. For example, alkyl-substituted imidazolium cations may include 1-butyl-3-methylimidazolium (BMIM), 1-ethyl-3-methylimidazolium (EMIM), 1-butyl-2,3-dimethylimidazolium (DBMIM), 1-octyl-3-methylimidazolium (OMIM), 1,3-di(N,N-dimethylaminoethyl)-2-methylimidazolium (DAMI), 1-decyl-3-methylimidazolium (DMIM), 1-dodecyl-3-methyl-dodecylimidazolium, and 1-butyl-2,3-dimethylimidazolium (BMMIM). Pyridine-derived N-heterocyclic cations may include 4-methyl-N-butyl-pyridinium (MBPy) or N-octylpyridinium (C8Py). The fluorinated counter anion may include tetrafluoroborate (BF4), hexafluorophosphate (PF6), bis-trifluoromethanesulfonimide (NTf2), or trifluoromethanesulfonic acid (OTf). The quaternary ammonium cation may include tetraethylammonium (TEA) or tetrabutylammonium (TBA). The sulfated counter anion may include hydrogen sulfate (HSO4), methyl sulfate (MeOSO3), trifluoromethyl sulfate (CF3OSO3), ethyl sulfate (EtOSO3), or perfluoroethyl sulfate (CF3CF2OSO3). In a preferred embodiment, the ionic liquid is 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIM) (BF4). EMIM-BF4 is commercially available from Sigma Aldrich.
[0065] An exemplary method for producing a piezoelectric film with an ionic liquid is shown in FIG. 11. The method begins with combining a raw piezoelectric polymer (or raw piezoelectric copolymer) with an aprotic solvent (such as dimethylformamide (DMF), dimethylacetamide, dimethylsulfoxide (DMSO), or 1-methyl-2-pyrrolidone (NMP)) with a suitable amount of ionic liquid, as in step 10. In a preferred embodiment, the piezoelectric polymer is PVDF, the aprotic solvent is DMF, and the ionic liquid is 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIM) (BF4). The ingredients are blended together with heating to produce a slurry, as shown in step 20. Typically, only 2-10 wt. % aprotic solvent is required to produce a usable melt. The ingredients only need to be heated to about 70° C. with regular stirring, such as with a Teflon paddle. It is also possible to produce a melt of only PVDF and (EMIM)(BF4) by starting with a dry mixture (i.e., no solvent) and increasing the temperature to about 180°C; however, casting this hot mixture requires a specially fabricated die. Once the slurry is prepared, it can be cast onto the web / release agent using a roll-to-roll process of the type described in U.S. Pat. No. 6,930,818 (incorporated by reference in its entirety). In a preferred embodiment, the web / release agent is PET and the slot die is only about 5 μm above the surface of the web (see steps 30 and 40). The web with the cast piezoelectric polymer / ionic liquid slurry is then moved to an oven area where the DMF is stripped off using heat (about 160°C), as shown in step 50. The coated web is allowed to cool, at which point the piezoelectric film with the ionic liquid can be peeled off the web, or the web can be sliced into portions for later use, i.e., as shown in step 60.
[0066] The resulting piezoelectric material has a high percentage of beta phase (see example), as shown in Figures 2A-3D, and can be poled using strong localized electric fields. As discussed above, it is known that piezoelectric films can be stimulated to move between polarization states using a variety of external stresses, such as mechanical stretching, heat, electromagnetic fields, and applied forces. The piezoelectric effect is closely related to the occurrence of electric dipole moments in solids. The dipole density or polarization (P) corresponds to the dipole moment / volume of the crystallographic unit cell and is typically expressed as C / m 2 The resulting dipole density P is measured as a function of the polarization of the material. The resulting dipole density P is a vector field (i.e., differential polarization) that is characteristic for a particular region of the material. Similar to magnets, dipoles in the vicinity of each other tend to align in regions (Weiss domains). The Weiss domains in the piezoelectric films of the present invention are primarily clusters of beta phase aligned together. When first produced, the domains in the larger film are usually randomly oriented (into or out of the film surface, laterally, etc.). However, using various multi-step processes, the domains can be aligned to produce localized areas of differential polarization. The process of these regions being aligned is known as poling.
[0067] An exemplary method for poling a thin film of piezoelectric polymer with ionic liquid is illustrated in Figures 2A-2D. As shown in Figures 2B and 2C, a thin film of piezoelectric material 210 can be polarized using a high voltage corona discharge 230 with spatial focusing. Suitable corona discharge equipment is available, for example, from Simco-Ion (Alameda, CA). Such devices can generate a localized 10-50 kV field, e.g., a 30 kV field, e.g., a 20 kV field, that can be brought within a few microns of the piezoelectric material to be polarized. Spatial focusing can be achieved using a steering electric field and / or gas flow, which focuses / steers the flux of ions emanating from the corona discharge. As shown in Figure 2B, the high voltage corona discharge 230 can be moved in three dimensions to generate areas of differential polarization, i.e., pattern the piezoelectric material 210. Alternatively, the piezoelectric material 210 can be mounted on an XYZ stage that allows the film workpiece to approach the high voltage corona discharge 230 in a controlled manner. In an alternative embodiment, a conductive mask 240 can be used to protect areas of the piezoelectric material 210 from the high voltage corona discharge 230, as shown in FIG. 2C. The conductive mask can be made, for example, of conductive stainless steel or another conductive material that can withstand proximity to a corona discharge. Alternative masks made of charge absorbing or charge blocking materials such as glass, plastic, or rubber would also work. When the high voltage corona discharge 230 is moved over the thin film of piezoelectric material 210, the thin film of piezoelectric material 210 is polarized only in areas where the conductive mask 240 does not cover the thin film of piezoelectric material 210. In addition, the polarity of the high voltage corona discharge 230 can be reversed such that some areas are polarized in a first direction, some areas are polarized in a second direction, and some areas can be randomly polarized or unpolarized. See also Figures 3A-3D.
[0068] Using the technique shown in Figures 2B and 2C, it is straightforward to produce a thin film of piezoelectric material 210 with areas of differential polarization P1 and P2, shown as 260 and 270 in Figure 2D. The areas of differential polarization 260 and 270 do not necessarily have equal magnitude and opposite polarity, however, such an arrangement generally provides a better contrast ratio when a two-particle electrophoretic medium is used with the thin film of piezoelectric material 210. For example, as shown in 2D, a first area 260 may be polarized toward the viewer, while a second area 270 may be polarized away from the viewer. This technique is further illustrated in Figures 3A-3D, which show how a single area 360 of a thin film of piezoelectric material deposited on a substrate 320 may be polarized to have a polarization vector pointing out of the page, as shown in Figure 3B. Thus, when the thin film of piezoelectric material is manipulated (bent), it will preferentially drive one polarity of the electrophoretic particles towards the viewing surface. As shown in FIG. 3C, a second area 370 of the thin film of piezoelectric material can be polarized in different directions, with or without the addition of a conductive mask 340, resulting in several patterned combinations of polarity and magnitude, as needed for the application. As shown in FIG. 3D, some parts of 370 are polarized towards the viewing surface, but shading is created by the conductive mask 340. Thus, when the piezoelectric material is manipulated (bent), it will preferentially drive one polarity of the electrophoretic particles towards the viewing surface, except in the areas where the polarization is masked, which will remain in a neutral color stage, thereby giving rise to a certain pattern, for example, a security seal.
[0069] 2A-3D illustrate various techniques that may be used to create areas of differential polarization in a thin film of piezoelectric material 210. As illustrated in FIGS. 4A-4D, these same techniques can also be used to create areas of differential polarization in a thin piezoelectric medium film 405. As shown in FIG. 4A, a thin film of piezoelectric material 410 can be bonded to a layer of electrophoretic microcell 420 to create a piezoelectric medium film 405. The thin film of piezoelectric material 410 can be bonded to the layer of electrophoretic microcell 420 using an adhesive layer (not shown) or the thin film of piezoelectric material 410 can be directly, i.e., slot coated, onto the layer of electrophoretic microcell 420 as discussed above with respect to FIG. 2A. Electrophoretic microcell 420 is typically formed from a polymer such as an acrylate, vinyl ether, or epoxide, as described in detail in, for example, U.S. Patent Nos. 6,930,818, 7,052,571, 7,616,374, 8,361,356, and 8,830,561, all of which are incorporated by reference in their entireties. In some embodiments, a layer of electrophoretic microcell 420 may be filled with an electrophoretic medium 425 that typically includes two or more electrophoretic particles 423 and 427 having different electrophoretic mobilities and optical properties. The electrophoretic medium 425 may be sealed with a sealing layer 430, preferably a water-soluble sealing layer, as described in U.S. Patent Nos. 7,560,004, 7,572,491, 9,759,978, or 10,087,344, all of which are incorporated by reference in their entirety. In some embodiments, a layer of electrophoretic microcells 420 is produced on a release material, filled with electrophoretic medium 425, and sealed with a sealing layer 430, and the filled and sealed electrophoretic microcells 420 are then used as a substrate for the production of a thin film of piezoelectric material 410. The resulting structure is a thin piezoelectric medium film 405. In other embodiments, the thin film of piezoelectric material 410 is laminated to an acrylate, vinyl ether, or epoxide film that is a precursor to the layer of electrophoretic microcells 420.The combined thin film of piezoelectric material 410 and precursor material is then embossed on the precursor side (discussed below) and subsequently filled with electrophoretic medium 425 and sealed with sealing layer 430 to produce thin piezoelectric medium film 405. In yet another embodiment (not shown in FIGS. 4A-4D ), a complete microcellular front plane laminate of the type described in U.S. Pat. No. 7,158,282 and commercially available from E Ink Corporation can be used as a substrate for the thin film of piezoelectric material 410, which can be poled as described below. Notably, when a front plane laminate material is used, the final structure additionally includes a conductive layer, which is typically optically transparent. The front plane laminate can be oriented so that the optically transparent electrode layer is in contact with the thin film of piezoelectric material 410, or the front plane laminate can be flipped over so that the sealing layer is in contact with the thin film of piezoelectric material 410.
[0070] Once the thin piezoelectric medium film 405 has been produced, the thin film of piezoelectric material 410 can be addressed as described with respect to Figures 2A-3D above. That is, the thin film of piezoelectric material 410 can be polarized using a high-voltage corona discharge 230 with spatial focus, as shown in Figure 4B, for example, by mounting the thin piezoelectric medium film 405 on an XYZ stage that allows the film workpiece to approach the high-voltage corona discharge 230 in a controlled manner. In an alternative embodiment, a conductive mask 240 can be used to protect areas of the thin piezoelectric medium film 405 from the high-voltage corona discharge 230, as shown in Figure 4C. As discussed with respect to Figures 2A-3D, the polarity of the high-voltage corona discharge 230 can be reversed, so that some areas are polarized in a first direction, some areas are polarized in a second direction, and some areas can be randomly polarized or unpolarized. As in FIG. 2D above, poling the thin film of piezoelectric material 410 in the thin piezoelectric medium film 405 results in areas of polarization P1 and P2 exhibiting differences shown as 460 and 470 in FIG. 4D. Importantly, because the thin piezoelectric medium film 405 can be fabricated prior to poling, it is feasible for the end customer to control the final step of creating the desired polarization design in the thin piezoelectric medium film 405. Thus, if the end product will include a security seal or serial number, the security seal or serial number can be installed after the end product is completed and verified, etc. For example, a U.S. $100 bill is printed in metallic ink at the U.S. Treasury along with a serial number, while at the same time the security ribbon comprising the thin piezoelectric medium film 405 can be polarized to create a verification code corresponding to the serial number. This feature eliminates many logistical issues and associated costs, for example, since there is no need to match prefabricated security markers to specific products further down the supply chain.
[0071] The techniques described above can be used to achieve a wide variety of thin piezophoretic films, as illustrated in the following figures.
[0072] As shown in Figures 5A-6B and 8A-10C, a piezoelectric film or display includes a layered stack of a number of components including a thin piezoelectric film and a layer of electrophoretic medium. The piezoelectric material can be PVDF-EMIM-BF4, however, any of the materials listed above can be used as they can be fabricated into very thin films. The electrophoretic medium typically includes one or more sets of charged particles that move through a non-polar solvent in the presence of an electric field. The electrophoretic medium is typically contained within a microcapsule, microcell, or dispersed droplet. The electrophoretic medium can also be contained within an open valley or well sealed within a larger flexible container. The piezoelectric films and displays exemplified herein can be made very thin, e.g., 100 μm or less in thickness, e.g., 70 μm or less in thickness, e.g., 50 μm or less in thickness, e.g., 35 μm or less in thickness, e.g., 20 μm or less in thickness, e.g., 10 μm or less in thickness. Such thin materials can bend without breaking or leaking, and are unnoticeable when incorporated into a final product such as paper or banknotes. In addition, many of the piezoelectric films or displays include layers, all of which are optically transparent and / or thin enough to be optically transparent, thus allowing the piezoelectric response to be viewed from above and below. In such piezoelectric films or displays, when a first image is visible from the top surface, e.g., position 1 in FIG. 1B, the bottom surface will typically show an inverted image, e.g., position 3 in FIG. 1B. However, when incorporating more than two types of particles in the electrophoretic medium, the top and bottom may not show the inverse image due to mixed particle conditions at one of the two surfaces.
[0073] Piezophoretic films or displays often include at least one electrode layer, which may be optically transparent and which may be flexible. Suitable materials include commercial ITO-coated PET, which may be used as a substrate for fabrication. In some other embodiments, flexible and transparent conductive coatings including other transparent conductive oxides (TCOs) may be used, such as zinc oxide, zinc tin oxide, indium zinc oxide, aluminum zinc oxide, indium tin zirconium oxide, indium gallium oxide, indium gallium zinc oxide, or fluorinated versions of these oxides, such as fluorine-doped tin oxide. In many of the embodiments described herein, poly(3,4-ethyleneoxythiophene) polystyrene sulfonate (PEDOT:PSS) is used because it has excellent bending properties and is optically transparent. Although the overall conductivity is not as high as, for example, PET / ITO, PEDOT:PSS is sufficient to provide the electric field required to drive electrophoretic particles in the electrophoretic medium. Other materials include polymers, typically light-transmitting polymers doped with conductive materials such as carbon black, metal flakes, metal whiskers, carbon nanotubes, silicon nitride nanotubes, or graphene. In some cases, the electrode layer is a metal film, such as a copper, silver, gold, or aluminum film or foil. Polymer films coated with metals may also be suitable for use as electrode layers. The resistance of the electrode layer may be 500 ohm-meters or less, e.g., 100 ohm-meters or less, e.g., 1 ohm-meter or less, e.g., 0.1 ohm-meters or less, e.g., 0.01 ohm-meters or less. (For comparison, electrophoretic medium layers typically have a resistance of about 10 7 ~10 8 The piezoelectric material has a resistance of 10 Ohm meters. 11 ~10 14 It has a resistance in ohms.)
[0074] A piezophoretic film or piezophoretic display will often include at least one adhesive layer formed from a polymer such as acrylic or polyurethane, polyurethane, polyurea, polycarbonate, polyamide, polyester, polycaprolactone, polyvinyl alcohol, polyether, polyvinyl acetate derivatives such as poly(ethylene-co-vinyl acetate), polyvinyl fluoride, polyvinylidene fluoride, polyvinyl butyral, polyvinyl pyrrolidone, poly(2-ethyl-2-oxazoline), acrylic or methacrylic copolymers, maleic anhydride copolymers, vinyl ether copolymers, styrene copolymers, diene copolymers, siloxane copolymers, cellulose derivatives, gum arabic, alginic acid, lecithin, polymers derived from amino acids, etc. The adhesive may additionally include one or more low dielectric polymers or oligomers, ionic liquids, or conductive fillers such as carbon black, metal flakes, metal whiskers, carbon nanotubes, silicon nitride nanotubes, or graphene. Adhesives containing such charged and / or conductive materials are conductive adhesives. The polymers and oligomers used in the adhesive layer may have functional groups for chain extension or crosslinking during or after lamination. The adhesive layer may be approximately 10 6 ohm*cm~10 8 Ohm*cm, preferably 10 12 It may have a resistivity value of less than ohm*cm.
[0075] Of the above mentioned polymers and oligomers, polyurethanes, polyureas, polycarbonates, polyesters and polyamides, especially those equipped with functional groups, are preferred due to their better adhesive and optical properties and high environmental resistance. Examples of functional groups may include, but are not limited to, -OH, -SH, -NCO, -NCS, -NHR, -NRCONHR, -NRCSNHR, vinyl or epoxides, and derivatives thereof, including cyclic derivatives. "R" in the above mentioned functional groups may be hydrogen or alkyl, aryl, alkylaryl or arylalkyl of up to 20 carbon atoms, which alkyl, aryl, alkylaryl or arylalkyl may be optionally substituted or interrupted by N, S, O or halogen. "R" is preferably hydrogen, methyl, ethyl, phenyl, hydroxymethyl, hydroxyethyl, hydroxybutyl, etc. Functionalized polyurethanes, such as hydroxyl terminated polyester polyurethanes or polyether polyurethanes, isocyanate terminated polyester polyurethanes or polyether polyurethanes, or acrylate terminated polyester polyurethanes or polyether polyurethanes, are particularly preferred.
[0076] In many embodiments, the piezoelectric film or display will often include a release sheet. The release material may be used temporarily to facilitate processing of the piezoelectric film or display, for example, when embossing, filling, cutting, etc. In other embodiments, the release material may be used to deliver the final piezoelectric film or display that will be adhered to the final product. In some cases, the release material will protect a functional adhesive layer that will be used to manipulate the piezoelectric film or display prior to the piezoelectric film or display being placed in the final product. The release material may be formed from a material selected from the group consisting of polyethylene terephthalate (PET), polycarbonate, polyethylene (PE), polypropylene (PP), paper, and lamination or cladding films thereof. The release material may be metallized to facilitate quality control measurements and / or to control static electricity during handling, shipping, and downstream incorporation into products. In some embodiments, a silicone release coating may be applied over the release material to improve release properties.
[0077] Although not shown in Figures 5A-6B and 8A-10C, the piezoelectric film or display may include an additional edge seal and / or barrier material that allows the piezoelectric film or display to maintain a desired humidity level, for example, to prevent leakage of non-polar solvents or adhesives, and to prevent intrusion of water, dust, or gas. The barrier material can be any flexible material, typically a polymer with low to negligible WVTR (water vapor transmission rate). Suitable materials include polyethylene terephthalate, polyethylene naphthalate, polycarbonate, polyimide, cyclic olefin, and combinations thereof. If the piezoelectric film or display will be exposed to particularly harsh conditions, a flexible glass such as WILLOW® glass (Corning, Inc.) can be used for the barrier layer. The edge seal can be a metallized foil or other barrier foil that is covered and adhered over the edge of the piezoelectric film or display. The edge seal may also be formed from a dispensed sealant (heat, chemical, and / or radiation cured), polyisobutylene, or an acrylate-based sealant, which may be crosslinked. In some embodiments, the edge seal may be a sputtered ceramic, such as alumina or indium tin oxide, or an advanced ceramic, such as those available from Vitex Systems, Inc. (San Jose, Calif.).
[0078] In general, the layers of the piezoelectric film 501-504 can be arranged / stacked in the order that produces the best performance for the end application. For example, as shown in FIG. 5A, the piezoelectric film 501 can be prepared by placing microcell precursor material on a release material 510 that includes a release material adhesive 520. The microcell precursor can then be embossed or photolithographically processed to produce an array of microcells 530. The microcells 530 can be thermally cured or cured using electromagnetic radiation such as UV light. The microcells 530 can then be filled with an electrophoretic medium and sealed with a sealing layer 540, as discussed above with respect to FIG. 4A. (It should be understood that the microcells 530 adjacent to the sealing layer 540 are filled with an electrophoretic medium comprising charged particles in a non-polar solvent, although the electrophoretic medium is not shown in subsequent figures.) The piezoelectric layer 560 can be laminated to the sealing layer 540 using an adhesive 550, which will typically be an optically transparent adhesive formed from one of the materials listed above. Finally, a flexible electrode 580 will be bonded to the piezoelectric film using a conductive adhesive 570. Such a piezoelectric film 501 can then be manipulated by handling the release material 510 until such time that the stack without the release material 510 is attached to the final product. In the piezoelectric film 501, the piezoelectric layer 560 is typically polarized to produce areas of polarization that exhibit a difference before the flexible electrode 580 is bonded to the piezoelectric film. In some embodiments, the flexible electrode 580 and the conductive adhesive 570 can be replaced with a thin layer of transparent conductive oxide, such as ITO. The ITO can be sputtered directly onto the piezoelectric layer 560 .
[0079] A closely related, but alternative stack is shown in Figures 5B-5D. In Figure 5B, a piezoelectric film 502 is produced in which a piezoelectric layer 560 is prepared prior to fabrication on a separate release material 510. For example, the piezoelectric layer 560 can be a PVDF-ionic liquid film poled to produce a security pattern. The piezoelectric layer 560 is then bonded to a sealed microcell layer 530, which is already bonded to a flexible electrode 580. Notably, in the piezoelectric film 502, the openings of the microcell layer 530 face away from the piezoelectric layer 560, which can promote good bonding between the microcell layer 530 and the piezoelectric layer 560. This bonding can be improved with the introduction of a primer 535 to improve adhesion of the piezoelectric layer 560 to the microcell material, typically a polymer comprising an acrylate, vinyl ether, or epoxide. Primer 535 can be a polar oligomeric or polymeric material, such as a polyhydroxy-functionalized polyester acrylate (e.g., BOMAR® BDE1025 from Dymax) or an alkoxylated acrylate, such as ethoxylated nonylphenol acrylate (e.g., SR504 from Sartomer), ethoxylated trimethylolpropane triacrylate (e.g., SR9035 from Sartomer), or ethoxylated pentaerythritol tetraacrylate (e.g., SR494 from Sartomer). Examples of polar polymers that are suitable for use as primer 535 include solvent urethane polymers, such as Irostic® polymers.
[0080] Of course, it is also possible to construct the stack such that the openings of the microcell layer 530 face towards the piezoelectric layer 560, as in the piezoelectric film 504 illustrated in Figure 5D. As a further alternative, shown in Figure 5C, the piezoelectric film 503 is positioned such that the openings of the microcell layer 530 face away from the piezoelectric layer 560, however the piezoelectric layer 560 is directly bonded to the flexible electrode 580.
[0081] The piezoelectric films (501, 502, 503, 504) shown in Figures 5A-5D can be converted into piezoelectric displays (601, 602) with the addition of a second flexible electrode 680 instead of the release layer in Figures 5A-5D. The piezoelectric displays (601, 602) will typically also include a second conductive adhesive 670, however, it should be noted that in some cases, the conductive adhesive 670 alone may be sufficient to provide the electric field required to switch the electrophoretic material. In addition, it is also possible to directly coat the bottom of the microcell layer 530 (Figure 6A) or the sealing layer 540 (Figure 6B) with a thin layer of transparent conductive oxide to create the second electrode. Furthermore, a conductive metal foil can be used as the second flexible electrode 680 if it is not necessary to be visible through both the top and bottom of the piezoelectric displays (601, 602). As shown in Figures 6A and 6B, it is typical to add a release material 510 to the completed piezoelectric display (601, 602) to improve handling and provide an easy to use adhesive for attaching the piezoelectric displays (601, 602). In some embodiments, the piezoelectric display 601 can be formed by simply bonding the piezoelectric layer 560 to a commercial front plane laminate, which includes a second flexible electrode 680 and a sealed microcell layer 530 containing the electrophoretic medium. In such cases, the piezoelectric layer 560 is typically polarized to create areas of differential polarization before the front plane laminate is bonded to the piezoelectric layer 560. Although the piezoelectric display (601, 602) of Figures 6A and 6B is shown with a piezoelectric layer 560 above the sealed microcell layer 530, it should be understood that the piezoelectric layer 560 can also be placed below the sealed microcell layer 530 to produce a piezoelectric display similar to Figures 5B and 5D.
[0082] A method of incorporating a piezoelectric polymer film containing an ionic liquid into a thin piezoelectric phoretic film 801 (see FIG. 8A) is described with respect to FIG. 7. First, a thin film 960 of piezoelectric polymer and ionic liquid is produced as described above. In step 720, the piezoelectric film 960 is removed from the substrate. The piezoelectric film 960 can be 10 μm or less thick, for example 5 μm or less thick, for example 3 μm or less thick. Typically, it is not necessary to stretch the piezoelectric film to increase the number of beta phase domains, but this is not excluded from the process. The piezoelectric film 960 is then poled using a suitable electric field, as discussed above. In step 730, a release material 910 is provided along with an adhesive 920, which is then laminated to the piezoelectric film 960 in step 740. The piezoelectric film 960 is then coated / bonded to an electrophoretic layer in step 750. The electrophoretic layer can be a sealed microcell layer including filled microcells 930 and a sealing layer 940, as shown in Figures 9A and 9B, or alternatively, the electrophoretic layer can include an encapsulated electrophoretic medium 990 in a polymer binder 995. Bonding of the piezoelectric film 960 to the electrophoretic layer can be facilitated with an intervening primer layer 935, for example, using one of the primer materials discussed above. If the electrophoretic layer is a sealed microcell layer, the microcells 930 can be positioned such that the sealing layer 940 is adjacent to the piezoelectric film 960 (as in Figure 8A), or the microcells 930 can be positioned such that the sealing layer 940 is positioned on the opposite side from the piezoelectric film 960 (i.e., as in Figure 8B). As a final step 760, an electrode layer 980 is produced, either bonded to / deposited on the microcell 930, as in Figure 8A, or bonded to / deposited on the seal layer 940, as in Figure 8B. As described above, the electrode layer 980 may comprise a flexible conductive material such as PEDOT:PSS, or may comprise a directly deposited (e.g., sputtered or evaporated) transparent conductive oxide (TCO).In some embodiments, the electrode 980 may comprise a prefabricated film of ITO on a polymer substrate such as PET. The piezoelectric film 801, including the directly deposited TCO electrode layer 980, the thin piezoelectric layer 960, and the thin layer of microcells 930 (approximately 10 μm thick), is remarkably thin (i.e., less than 25 μm thick, excluding the release material 910), which allows the piezoelectric film 801 to bend without breaking and is unnoticeable when attached to an object such as a banknote. The corresponding piezoelectric film 901 including microcapsules can also be fabricated with a total thickness of less than 25 μm. Of course, alternative structures using a thin piezoelectric film 960 are also possible, such as positioning the piezoelectric film 960 between the electrode 980 and the electrophoretic layer, i.e., the layer of microcapsules 990, as shown in FIG. 9B. Alternatively, the electrode 980 in FIGS. 8A-9B may be replaced with a conductive adhesive (not shown) or a conductive adhesive along with an additional release layer (not shown).
[0083] Similar to Figures 6A and 6B, the piezoelectric films of Figures 8A-9B can include a second electrode layer to form a corresponding display (1001, 1002, 1003), as shown in Figures 10A-10C. Both the electrode layer 980 and the second electrode layer 1080 can comprise a flexible conductive material such as PEDOT:PSS, or both the electrode layer 980 and the second electrode layer 1080 can comprise a directly deposited (e.g., sputtered or evaporated) transparent conductive oxide (TCO), or some combination thereof. Again, in the case where both the electrode layer 980 and the second electrode layer 1080 use a thin TCO film, the resulting piezoelectric display (1001, 1002, 1003) can be made very thin, i.e., less than 25 μm thick, excluding the release material 910. In some embodiments, the electrode layer 980 is produced bonded to / deposited on the microcell 930, as in Fig. 10A. In other embodiments, the electrode layer 980 is produced bonded to / deposited on the sealing layer 940, as in Fig. 10B. The assembly of piezoelectric displays 1001 and 1002 can also be used with microcapsules 990 containing an electrophoretic medium held together with a binder 995, thus producing piezoelectric display 1003, as shown in Fig. 10C. Alternatively, the electrodes 980 / 1080 in Figs. 10A-10C can be replaced with a conductive adhesive (not shown) or a conductive adhesive, along with an additional release layer (not shown).
[0084] It should be understood that the electrodes do not have to be bonded to the piezoelectric film prior to embossing the stack comprising the piezoelectric film and the microcell precursor material. Rather, a stack including a release material, an adhesive, a piezoelectric film, and a microcell precursor can be prepared, and the microcell precursor can then be embossed, filled, and sealed as described above. Alternatively, a stack including a release material, an adhesive, an electrode, a piezoelectric film, and a microcell precursor can also be prepared, and the microcell precursor can then be embossed, filled, and sealed as described above.
[0085] It should be understood that the piezoelectric film and piezoelectric display described herein can be combined with other known techniques for generating security markers or authenticity indicators. For example, the piezoelectric film or piezoelectric display may additionally include a translucent top layer that does not change optical properties when the piezoelectric film is manipulated. For example, a smiley face top layer may include eyes constructed from a piezoelectric display such that the eyes appear to blink when the layered material is bent. In some embodiments, an image or shape may be printed or laminated onto a monochromatic (e.g., white) background, and one must view through the piezoelectric film to see the pre-arranged pattern. Thus, when not in use, the viewer will see only a monochromatic color, i.e., the printed image or shape will be hidden. However, the printed image or shape will be displayed when the device is manipulated. It is also feasible to adhere the piezoelectric film or piezoelectric display to a separate light-transmitting polymer film contained within the target product (e.g., a banknote), so that the pattern in the piezoelectric layer is only visible when the target product is held up and manipulated relative to a light source.
[0086] (Example) A slurry of PVDF and 10% 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIM) (BF4) in DMF was produced with mixing and some application of heat above room temperature. The slurry was cast onto a PET web using a slot die coater about 5 μm above the web at a working speed of about 10 feet / min. The web was placed directly into a 160° C. oven where it appeared as a thin piezoelectric film after spending about 5 minutes. The resulting film was removed from the PET backing and mounted in a thin film mount for FTIR spectroscopy measurements. The IR absorption spectrum of the resulting PVDF-EMIM-BF4 film (star line) is shown in FIG. 12 in comparison with a commercial PVDF-TrVDF copolymer film from TE Connectivity (Norwood, MA) (triangle line), PVDF that was solution melted and cast in DMF (no ionic liquid) (open circle line), and PVDF that was solution melted and cast in DMF and then strained once the film was cooled (no ionic liquid) (open square line). [The cast and strained PVDF spectrum (open square line) is offset to make it easier to distinguish from the other spectra, however, the baseline is indeed very similar for the PVDF-TrVDF copolymer film and the PVDF-EMIM-BF4 film.]
[0087] As can be seen from the spectrum in Figure 12, the PVDF-EMIM-BF4 film of the present invention has excellent properties evidenced by high beta phase concentration. In particular, the 974 cm -1 Absorption at 1,280 cm is mainly absent for the PVDF-EMIM-BF4 film, whereas absorption at 1,300 cm is mainly absent for the PVDF-EMIM-BF4 film. -1 and 840 cm -1The beta peak at is prominent in the PVDF-EMIM-BF4 film as well as the copolymer and tensioned samples known to have a high percentage of beta domains. Rough estimates of the percentage beta phase based on the areas under the peaks shown with normalized baseline are: cast PVDF = 50% beta phase, PVDF-TrVDF copolymer film = 85% beta phase, cast and tensioned PVDF film = 80% beta, and PVDF-EMIM-BF4 film = nearly 90% beta phase. It is worth noting that the cast and tensioned PVDF film was not completely transparent in the optical spectrum, and showed some waviness when a light source was viewed through the film. The other three films were transparent to visible light and had good optical properties.
[0088] It will be apparent to those skilled in the art that numerous changes and modifications may be made to the specific embodiments of the invention described above without departing from the scope of the invention. Therefore, the whole of the foregoing description is to be interpreted in an illustrative sense, and not in a restrictive sense.
Claims
1. A piezoelectric film comprising polyvinylidene fluoride (PVDF) and less than 10% (w / w) ionic liquid.
2. The piezoelectric film of claim 1 , wherein the piezoelectric film is less than 10 μm thick.
3. The ionic liquids include alkyl-substituted imidazolium cations, alkyl-substituted pyridinium cations, pyridine-derived N-heterocyclic cations, fluorinated counter anions, sulfated counter anions, dicyanamide (N(CN) 2 ), quaternary ammonium cations, or a combination thereof.
4. the alkyl substituted imidazolium cation is 1-butyl-3-methylimidazolium (BMIM), 1-ethyl-3-methylimidazolium (EMIM), 1-butyl-2,3-dimethylimidazolium (DBMIM), 1-octyl-3-methylimidazolium (OMIM), 1,3-di(N,N-dimethylaminoethyl)-2-methylimidazolium (DAMI), 1-decyl-3-methylimidazolium (DMIM), 1-dodecyl-3-methyl-dodecylimidazolium, and 1-butyl-2,3-dimethylimidazolium (BMMIM); or The pyridine-derived N-heterocyclic cation is 4-methyl-N-butyl-pyridinium (MBPy) or N-octylpyridinium (C 8 Py), or The fluorinated counter anion is tetrafluoroborate (BF 4 ), hexafluorophosphate (PF 6 ), bis-trifluoromethanesulfonimide (NTf 2 ), or trifluoromethanesulfonic acid (OTf), or the quaternary ammonium cation is tetraethylammonium (TEA) or tetrabutylammonium (TBA); or The sulfated counter anion is hydrogen sulfate (HSO 4 ), methyl sulfate (MeOSO 3 ), trifluoromethyl sulfate (CF 3 OSO 3 ), ethyl sulfate (EtOSO 3 ), or perfluoroethyl sulfate (CF 3 CF 2 OSO 3 ) or The ionic liquid is 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIM) (BF 4 4. The piezoelectric film of claim 3 .
5. The piezoelectric film of claim 1 , wherein the piezoelectric film is optically transparent.
6. 10. The piezoelectric film of claim 1, further comprising a copolymer selected from trifluoroethylene (TrFE), hexafluoropropylene (HFP), and chlorotrifluoroethylene (CTFE).
7. 1. An electrophoretic display film of less than 100 μm thickness (top to bottom), said electrophoretic display film comprising, in order: A first adhesive layer (520); an electrophoretic medium layer (530); A patterned piezoelectric film (410, 560) according to claim 1, comprising zones of differential polarization (460, 470); A flexible light-transmitting electrode layer (580); An electrophoretic display film comprising:
8. 1. An electrophoretic display film of less than 100 μm thickness (top to bottom), said electrophoretic display film comprising, in order: A first adhesive layer (520); A patterned piezoelectric film (410, 560) according to claim 1, comprising zones of differential polarization (460, 470); an electrophoretic medium layer (530); A flexible light-transmitting electrode layer (580); An electrophoretic display film comprising:
9. 1. An electrophoretic display film of less than 100 μm thickness (top to bottom), said electrophoretic display film comprising, in order: An adhesive layer (520); an electrophoretic medium layer (530); A patterned piezoelectric film (410, 560) according to claim 1, comprising zones of differential polarization (460, 470); A conductive adhesive layer (570); An electrophoretic display film comprising:
10. the electrophoretic medium layer (530) comprises a plurality of microcapsules (990) containing a non-polar fluid (425) and charged pigment particles (423, 427) that move toward or away from the patterned piezoelectric film (410, 560) when the patterned piezoelectric film (410, 560) is bent, the microcapsules (990) being bonded together using a polymeric binder (995); or 10. An electrophoretic display film as claimed in any one of claims 7 to 9, wherein the electrophoretic medium layer (530) comprises a plurality of microcells (420) containing a non-polar fluid (425) and charged pigment particles (423, 427) that move towards or away from a patterned piezoelectric film (410, 560) when the patterned piezoelectric film (410, 560) is bent, the non-polar fluid (425) and charged pigment particles (423, 427) being sealed within the microcells using a sealing layer (430, 540).
11. 10. An electrophoretic display film according to any one of claims 7 to 9, wherein the electrophoretic display film is less than 50 μm thick.
12. 10. An electrophoretic display film according to any of claims 7-9, wherein the flexible light-transmitting electrode layer (580) comprises a metal oxide comprising tin or zinc, or poly(3,4-ethyleneoxythiophene) (PEDOT).
13. 10. An electrophoretic display film assembly comprising a release sheet (510) bonded to the electrophoretic display film of claim 7, the release sheet (510) being bonded to the first adhesive layer (520).
14. 14. The electrophoretic display film assembly of claim 13, further comprising a second adhesive layer bonded to the flexible light-transmissive electrode layer and a second release sheet bonded to the second adhesive layer.
Citation Information
Patent Citations
electro-optic display
JP2007509379A
Display device, method for manufacturing display device, and electronic paper
JP2008176196A
Piezoelectric electrophoretic display
JP2021517671A
Polyvinylidene Fluoride Having an Increased Melting Point
US20080281031A1